2014
DOI: 10.1016/j.rbr.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Características demográficas e clínicas de pacientes com artrite reumatoide no Piauí, Brasil – avaliação de 98 pacientes

Abstract: Features of rheumatoid arthritis obtained in this study are similar to those found in some national and international studies, but we observed higher female preponderance and illiteracy rate, in addition to a moderately severe erosive disease on average, with frequent sicca and other extra-articular manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…The sex ratio was found to be 6:1 for females:males in this study. According to a study conducted in Romania, the female:male ratio in RA patients was approximately 5:1,28 while another study reported a sex ratio of 2:1 29. The higher number of female RA patients could be explained by the fact that women produce a more robust immunoresponse to infection, which may be responsible for the higher risk of developing autoimmune diseases 30…”
Section: Discussionmentioning
confidence: 99%
“…The sex ratio was found to be 6:1 for females:males in this study. According to a study conducted in Romania, the female:male ratio in RA patients was approximately 5:1,28 while another study reported a sex ratio of 2:1 29. The higher number of female RA patients could be explained by the fact that women produce a more robust immunoresponse to infection, which may be responsible for the higher risk of developing autoimmune diseases 30…”
Section: Discussionmentioning
confidence: 99%
“…Minnock et al, did a longitudinal study with RA patients (n = 87) to know the correlation of fatigue and disease activity, results revealed fatigue is not explained by disease activity as represented by the ACR core set outcomes, rather it’s a behavioral variable with multifactorial influences. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Artrite Reumatoide é uma doença inflamatória crônica que se manifesta com lesão articular progressiva além de outros sintomas extra-articulares (BARBOSA et al, 2020;KOBAK 2011). De maneira global a AR se apresenta como uma patologia que envolve simetricamente as pequenas articulações, apresentando também como características a dor, limitação do movimento por mais de uma hora e rigidez matinal (ALMEIDA et al, 2014). Essa enfermidade acomete uma parcela de 0,5% a 1% da população aproximadamente.…”
Section: Resultsunclassified